Factoring and product formulas

Square of sum
(a+b)^2 = a^2 + 2ab + b^2
Find   It is known that:
      =   

Square of difference
(a-b)^2 = a^2 - 2ab + b^2
Find   It is known that:
      =   

Difference of squares
a^2 - b^2 = (a + b)(a - b)
Find   It is known that:
      =   

The cube of sum
(a+b)^3 = a^3 + 3a^2*b + 3ab^2 + b^3
Find   It is known that:
      =   

Cube of difference
(a-b)^3 = a^3 - 3a^2*b + 3ab^2 - b^3
Find   It is known that:
      =   

Sum of cubes
a^3 + b^3 = (a + b)(a^2 - ab + b^2)
Find   It is known that:
      =   

Difference of cubes
a^3 - b^3 = (a - b)(a^2 + ab + b^2)
Find   It is known that:
      =